Implementasi Kebijakan Merdeka Belajar Kampus Merdeka (MBKM) Universitas Negeri Surabaya - Winny Ronaulyk D; Vita Nur Alifa; Riska Hanum; Shelly Andari (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
The Independent Campus Learning Program (MBKM) is the foundation of universities in improving the quality of education and the quality of graduates. The MBKM program gives students the right to take part in off-campus learning for three semesters, and the programs that students can take part in during off-campus learning are student exchange, internship/work practice, KKN, entrepreneurship, academic research/research activities, independent study, and take part in campus teaching programs, and so on. This research aims to analyze the MBKM policy at UNESA in its implementation and how to face challenges in its implementation. This research uses a literature study approach (literature review). Researchers collect data by identifying, evaluating and synthesizing research relevant to the topic of MBKM Policy Implementation at UNESA. The results of the research show that UNESA has implemented the MBKM program well, in its implementation it is always supervised and monitored by the campus, and in facing existing challenges the campus always improves it. Students are also provided with work experience and practical skills that make individuals ready and competent to contribute to the world of work through the MBKM program.